Identifikasi Produk Unggulan Dan Kontribusi Sektor Tersier Di Kabupaten Madiun - Mintarti Indartini Indartini; Dian Pratiwi; ML Endang Edi Rahayu (Universitas Merdeka Madiun, 2020)
Madiun Regency is one of the districts in the western part of East Java which has a very strategic location as a transit city. Then the tertiary sector has a big role / contribution to Gross Regional Domestic Product / PDRB which certainly affects economic growth. This research was carried out in order to: (1) Identify the leading sectors of the tertiary sector in Madiun Regency. (2) Reviewing the contribution of tertiary sector to PDRB of Madiun Regency. and (3) Assessing the base sector which can be used as a mainstay for economic development in Madiun Regency, especially the tertiary sector in 2019 and in the future. The results of research using the analysis of Location Quotient (LQ) are (1) The tertiary sector of Madiun Regency is included in mainstay, superior and prospective criteria. (2) The superior potential of tertiary sector Madiun Regency are the information and communication sector, real estate, education services and health services and social activities. Based on analysis of contribution to the Gross Regional Domestic Product / PDRB of tertiary sector that has largest contribution is the financial and insurance services sector; second is the information and communication sector; and third is government administration, defense and social security is mandatory.Â Keywordsâ€”: Tertiary; Superior Product; Location Quotient (LQ); Contribution; Madiun Regency.